1990
DOI: 10.1002/ar.1092280302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of purified Pasteurella multocida dermonecrotoxin on cartilage and bone of the nasal ventral conchae of the piglet

Abstract: The effect of intramuscular injection of purified dermonecrotoxin (DNT) from Pasteurella multocida type D on the nasal ventral conchae of piglets was studied. Severe atrophy of the conchae was observed 4, 6, and 10 days after injection (p.i.d). Lesions were observed in conchae cartilage and bone. Cartilage changes observed were the absence of chondrocyte maturation and hypertrophy, hyaline cartilage invasion by fibroblast-like and multinucleated cells, and endothelium damage with haemorrhages along the cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…It is assumed that the mitogenic activity of PMT is related to its potent ability to promote bone resorption. In experimental studies in which PMT has been administered to experimental animals, bone resorption was associated with an increased number of osteoclasts in affected bones (1,14,21,73,74). A surprising finding was that intraperitoneal injection of PMT resulted in increased osteoclast density and bone loss both in the maxillofacial skeleton and in the appendicular skeleton of rats (73).…”
Section: Fig 3 the Possible Points Of Interaction Between Osteolytimentioning
confidence: 99%
“…It is assumed that the mitogenic activity of PMT is related to its potent ability to promote bone resorption. In experimental studies in which PMT has been administered to experimental animals, bone resorption was associated with an increased number of osteoclasts in affected bones (1,14,21,73,74). A surprising finding was that intraperitoneal injection of PMT resulted in increased osteoclast density and bone loss both in the maxillofacial skeleton and in the appendicular skeleton of rats (73).…”
Section: Fig 3 the Possible Points Of Interaction Between Osteolytimentioning
confidence: 99%
“…Inoculation of PMT alone is sufficient to generate all symptoms of atrophic rhinitis in animals [6]. Bone tissue is constantly rebuilt by the action of osteoblasts and osteoclasts [7].…”
Section: Introductionmentioning
confidence: 99%
“…Type D and A strains for example are associated with upper respiratory tract infections in pigs and toxigenic strains expressing the Pasteurella multocida Toxin (PMT) cause porcine atrophic rhinitis [2]. This disease is characterized by an atrophy of the nasal ventral conchae bones and a shortening or distortion of the snout [3]. After purification of the toxin in the late 1980s, it was shown that the purified toxin alone was sufficient to induce bone lesions and thus must be the causative agent of porcine atrophic rhinitis [4,5,6].…”
Section: Introductionmentioning
confidence: 99%